Smoking in pregnancy: a systematic review of qualitative research of women who commence pregnancy as smokers. (19th December 2012) - Flemming, Kate; Graham, Hilary; Heirs, Morag; Fox, Dave; Sowden, Amanda
Abstract Aim To provide evidence on how women's circumstances and experiences influence their smoking behaviour in pregnancy, including their attempts to quit. Background Women in disadvantaged circumstances are more likely to smoke prior to pregnancy; they are also less likely to quit in pregnancy and, among those who quit, more likely to resume smoking after birth. Although there is a rich seam of qualitative research on their experiences, it has yet to be bought together and synthesized. Design The synthesis was conducted using meta‐ethnography. Data sources A comprehensive search of five electronic databases (inception to May 2012) was completed to identify qualitative research exploring pregnant women's experiences of smoking in pregnancy. Review methods Following critical appraisal, 26 studies reported in 29 papers were included in the review. Over 640 pregnant women were represented, the majority drawn from disadvantaged groups. We carried out the synthesis using meta‐ethnography. Results Four dimensions of women's circumstances and experiences of smoking in pregnancy were highlighted: the embeddedness of smoking in women's lives, questioned only because of pregnancy; quitting for pregnancy rather than for good; quitting had significant costs for the woman and cutting down was a positive alternative; the role of partners and the broader dynamics of the couple's relationship in influencing women's smoking habits. Conclusion Syntheses of qualitative research have an important role to play in producing the evidence base for midwifery, nursing, and public health policy and practice. The four dimensions identified in this review have implications for the design and delivery of interventions to support women to quit smoking in pregnancy.